Ethical Dilemmas in Patient Selection for a New Kidney Transplant Program in Guyana, South America - Guy, S.R.; Womble, A.L.; Jindal, T.R.; Doyle, A.; Friedman, E.A.; Elster, E.A.; Falta, E.M.; Jindal, R.M. (Transplantation proceedings, 2013)
We describe ethical/moral issues in patient selection in a new living donor kidney transplant program in Guyana, South America. Over 3 years, we screened 450 patients with chronic kidney disease among which 70 were suitable for kidney transplantation. There were five patients whose evaluations raised possible ethical dilemmas: one had nonadherence to dialysis; two of Guyanese origin living abroad wished to have the transplant performed in Guyana; a minor wished to donate to her mother; and another subject was considering commercialization of the transplant process. Since inception of the renal replacement program in 2008, we have completed 13 living kidney transplantations, 17 peritoneal dialysis placements, and 20 vascular access procedures. In the five patients wherein faced ethical dilemmas, three were rejected for consideration despite having living donors: one was nonadherent, the second excluded due to an attempt to commercialize the process, and the third, a minor who wished to donate to the mother. The other two patients were considered Guyanese ex-patriots acceptable for the program. The consequence of kidney failure in Guyana prior to introduction of renal replacement therapy was a virtual death sentence. These cases illustrate ethical dilemmas serving to throw into stark relief the implications of decisions made in a developing country versus those in a developing country.